Pengaruh Teori Motivasi Dua Faktor Herzberg Terhadap Kepuasan Kerja Karyawan Tetap Departemen Central Inbound PT Tiki JNE Jakarta - Bagas Jaka Pradana; Zafiratul Hasanah; Tia Rahmania (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Job satisfaction is a crucial element in maintaining employee productivity and loyalty, particularly in a dynamic logistics sector like PT Tiki JNE. Motivation and hygiene factors from Herzberg's Two-Factor Theory are believed to significantly influence job satisfaction. This study aims to analyze the influence of these two factors on job satisfaction of permanent employees in the Central Inbound Department of PT Tiki JNE Jakarta, while also addressing the gap in the literature regarding the application of this theory in the context of the Indonesian logistics industry. This research method uses a quantitative descriptive-correlational approach. It was conducted in the Central Inbound Division of PT Tiki JNE, Garuda Kemayoran branch, Central Jakarta. A total sample of 40 permanent employees (saturated sample) was selected. Data were collected through a closed-ended questionnaire based on Herzberg's Two-Factor Theory. Data analysis was conducted using SPSS with validity, reliability, normality, multicollinearity, heteroscedasticity, and multiple linear regression testing techniques to determine the effect of motivational and hygiene factors on job satisfaction, both partially and simultaneously. The results of the study showed that motivational and hygiene factors, as outlined in Herzberg's Two-Factor Theory, simultaneously had a positive and significant effect on job satisfaction for permanent employees in the Central Inbound Department of PT Tiki JNE Jakarta. Motivational factors such as achievement, recognition, responsibility, and self-development contribute to increasing job satisfaction, while hygiene factors such as company policies, supervision, and working conditions help prevent dissatisfaction. A strategic combination of increasing motivation and fulfilling hygiene factors is considered essential for creating a productive and sustainable work environment. These findings confirm the relevance of Herzberg's theory in the logistics context and the importance of a holistic approach to human resource management.